Resonance Attenuation of Ultrasonic Waves in a High Viscosity Magnetic Liquid - CHARAZIAK, Karolina; MARECKI, Marcin; HORNOWSKI, Tomasz; JÓZEFCZAK, Arkadiusz; SKUMIEL, Andrzej (Archives of Acoustics, 2008)
Ultrasonic waves attenuation as a function of frequency in a magnetic fluid APG-832 containing magnetite particles dispersed in a synthetic hydrocarbon was investigated. The measurements were carried out using broadband method in which ultrasonic pulse that has traveled through the sample is analyzed using a Fourier transform algorithm to determine the spectra of amplitude and phase and therefore to estimate the attenuation and dispersion of a given medium. Ultrasonic attenuation spectra of APG-832 magnetic liquid were measured between 1 and 10 MHz at 20 and 40±C. In the presence of the external magnetic field attenuation spectra at 20±C exhibited a single peak at frequency about 3 MHz. Experimental results were analyzed using concept of the resonance absorption of an ultrasonic wave in a magnetic fluid acted on by a magnetic field.